When Is a Bedroom Not a Bedroom? Bringing a Space of Flows to the Design of Apartment Interiors in YO! Home. Issue 4 (20th October 2015) - Chittenden, Tara
ABSTRACT: An apartment is commonly seen as a place. Accepting it as a process, the act of creating and performing interiors becomes a collaborative flow involving designers, makers, and users. Simon Woodroffe, British entrepreneur, recognized what the dynamic performance spaces of the theater could bring to the design of residential interiors and in 2012 he launched YO! Home—his reconceptualization of the city center apartment, drawing on the mechanisms of stage design to create fluid and changeable interiors. The ability to create a number of credible interactive environments from a single cubic space offers much potential to design interiors that are responsive to the multiple daily needs of inhabitants, especially those who need to optimize every centimeter of space. YO! Home promotes a reappraisal of the role of design in relation to the expressive and transformative possibilities of an apartment interior at the stage of material conception. In so doing it demonstrates the possibility to provide homes for more people within the same residential footprint, but also that those "shoebox dwellers" can get a lot more interior for their space. In this paper, I draw on Castells' concept of the space of flows as both metaphor and provocateur to help question the design of interiors that are shaped by the flows of inhabitants, and how these flows manifest in the prototype of YO! Home.